MULTILITERACIES IN SCHOOL AND THE UFES PIBID LETRAS-INGLÊS (PERcursos Linguísticos, 2021)
When thinking about public education in Brazil, it is natural to think about both regular schools and public universities. However, these institutions coexist in our society in a distant way. While many university professors in undergraduate courses claim to have had very little contact with basic education, many English undergraduate students cannot imagine taking on the role of teachers in the future, especially within public education. The Pibid – Institutional Program for Teaching Initiation Scholarships – provides dialogue between the university and public schools, and has shown how the relationship between basic and higher education could be closer. This article, originated from a scientific initiation research (PRPPG-Ufes 2019-2020) presents an analysis based on interviews with some former participants of the Ufes Pibid Letras-Inglês of how the undergraduate course in English can improve with this program  experiences, reiterating its importance for the education of future professionals and, consequently, for the benefit of society. Within this context, the construction of the English language teacher identity through Pibid and the presence of multiliteracies in the practices carried out in the program are also analyzed. The results obtained point to the strength of such program in the formative process of undergraduate students of Letras-Inglês at Ufes.Keywords: Pibid. English Language Teaching. Public school. Identity. Multiliteracies.